Evaluation of early growth and aluminum tolerance in Leucaena leucocephala (Lam.) de Wit seedlings under acidic conditions as a recommendation for post-coal mining land rehabilitation - Salim, Mohammad Agus; Sudrajat, Dede J.; Nugroho, Aditya; Indriani, Fitri; Rustam, Evayusvita; Maharani, Dewi; Rosdayanti, Henti; Wawangningrum, Hary; Efendi, Muhammad; Suhaendah, Endah; Mulyana, Ade Nendi; Wahyudi, Imam; Setyaningsih, Luluk; Budi, Sri Wilarso (Brawijaya University, 2026)
One of the problems with acidic soil is its high aluminum (Al) content, which can cause toxicity to plants. this study was conducted to evaluate the preliminary growth and tolerance of L. leucocephala seedlings to Al exposure. This study used a completely randomized design (CRD) with one factor, namely Al concentration, consisting of 5 levels (0, 2, 4, 6, and 8 mM). The evaluation of seedling growth and tolerance assessed included: height, root length, dry weight of roots and shoots, tolerance index, SPAD (Soil Plant Analysis Development) chlorophyll, and photosynthesis rate. The results showed that Al exposure reduced all growth parameters (height, root length, dry weight of roots and shoots) of L. leucocephala seedlings. The tolerance index of L. leucocephala seedlings also decreased significantly (up to 43.68%) with increasing Al concentration. Meanwhile, chlorophyll and photosynthesis rate parameters increased with Al exposure of 2-4 mM, but decreased with higher Al exposure (6-8 mM). The threshold value or sensitivity of L. leucocephala seedlings to Al exposure was less than two mM. The L. leucocephala species can also serve as an alternative for land rehabilitation with high Al content as post-coal mining land.